(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This research examined how Rational Emotive Behavioural Therapy can help reduce the propensity of undergraduates to cybercrime in north central, Nigeria. It has raised two research questions and it has formulated and tested two null hypothesis. The study design incorporated quasi experimental non equivalent control group; it was conducted within three randomly picked faculties in the University of Abuja. A sample of 361 out of the 6416 students was selected which created a population in the form of 53 vulnerable undergraduate students to cybercrimeThe research questions were answered using descriptive statistics, and a one-sample t-test was used to test the null hypotheses. The analysis revealed that students in the control group were more susceptible to cybercrime than those in the experimental group. There was a significant difference between the pre-test and post-test mean scores of the experimental group regarding their susceptibility to cybercrime. The interactive effect of the treatment plan was not gender-discriminative, with positive results observed for both males and females. It was reasoned that the application of Rational Emotive Behavioural Therapy will turn susceptible students to become non-susceptible students in the event of cybercrime. The strategy will also help undergraduates in Nigeria to grow negative attitude towards cybercrime.